Nest Gasses as a Potential Attraction Cue for Biting Flying Insects and Other Ectoparasites of Cavity Nesting Birds - Castaño-Vázquez, Francisco; Merino, Santiago; Cuezva, Soledad; Sánchez-Moral, Sergio (Frontiers in Ecology and Evolution, 2020)
The presence of nestlings and other nest dwelling organisms in cavity nests alters the composition of gasses inside the cavity. Differential concentrations of gasses could be used by some parasites as a cue to localize their hosts. Here, we explored temporal variation in the concentration and isotopic signature of carbon dioxide (CO2) and methane (CH4) inside nest boxes of blue tits (Cyanistes caeruleus) during the nestling period (on days 3, 8, 13, 20, and 21 post-hatching) as well as several variables potentially affecting such variation. Finally, we checked whether differences in gas concentrations affect the abundance of different types of parasites affecting nestlings. Gas concentration and isotopic signature were significantly different between nest boxes and the forest during the nestling period. The CO2 concentration was higher inside nests than in the forest air, whereas CH4 concentration was lower. We expected to observe a positive correlation between the abundance of parasites actively seeking nests (i.e., blackflies, biting midges, and blowflies) and differences in gas concentration for those species that use these differences as a cue for host location. We observed that biting midge abundance was positively related to differences in CO2 between nest and forest air at day 20 of nestling age, indicating that this species can use these differences to locate hosts. We also found a positive relationship between blackfly abundance and differences in CH4 concentration. However, we hypothesize that the concentration of this gas inside nests may be related with bacterial activity; therefore, this relationship may be due to an effect of bacteria on blackflies and not to the effect of CH4 as an attraction cue for blackflies.